2012
DOI: 10.1002/cncr.27866
|View full text |Cite
|
Sign up to set email alerts
|

18F‐Fluorodeoxyglucose positron emission tomography/computed tomography for the detection of recurrent bone and soft tissue sarcoma

Abstract: BACKGROUND: The clinical utility of modern hybrid imaging modalities for detecting recurrent bone or soft tissue sarcoma remains to be determined. In this report, the authors present a clinical study on the diagnostic accuracy and incremental value of integrated 18F‐fluorodeoxyglucose positron emission tomography/computed tomography (18F‐FDG PET/CT) in patients with a history of sarcoma who have clinically suspected disease recurrence. METHODS: Forty‐three patients who had a history of bone or soft tissue sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Franzius et al (42) used similar criteria and reported identical results; however, their study consisted exclusively of patients with primary bone sarcoma (either Ewing sarcoma or osteosarcoma). A recent study by Al-Ibraheem et al (39) of a mixture of adult and pediatric soft-tissue and bone sarcomas found local recurrence in six of seven patients (sensitivity = 86%), whereas contrast-enhanced CT had a sensitivity of only 43%.…”
Section: Local Disease Recurrencementioning
confidence: 92%
See 1 more Smart Citation
“…Franzius et al (42) used similar criteria and reported identical results; however, their study consisted exclusively of patients with primary bone sarcoma (either Ewing sarcoma or osteosarcoma). A recent study by Al-Ibraheem et al (39) of a mixture of adult and pediatric soft-tissue and bone sarcomas found local recurrence in six of seven patients (sensitivity = 86%), whereas contrast-enhanced CT had a sensitivity of only 43%.…”
Section: Local Disease Recurrencementioning
confidence: 92%
“…MR imaging is commonly used to detect local recurrence after limb salvage, demonstrating localized or nodular contrast enhancement; however, false-positive results can occur due to enhancing scar tissue, reactive hyperemia, or capillary sprouting (39). In addition, the utility of MR imaging is limited in patients with metallic implants or fixation.…”
Section: Local Disease Recurrencementioning
confidence: 99%
“…Furthermore, PET scan images are often fused with cross-sectional CT imaging (PET/CT) to provide functional and anatomical imaging. There have been several applications of FDG-PET to soft tissue sarcoma including grading of tumors, initial staging [15], assessing response to neoadjuvant therapy [16], determining prognosis [16, 17], and investigating potential local recurrence [18] (Figure 1). In a recent publication evaluating the diagnostic and prognostic value of the PET/CT in sarcoma, it was found that the test is highly sensitive and specific in the detection of high-grade bone and soft tissue sarcoma but had a low positive predictive value for evaluation of nodal metastases [19].…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…Studies on the use of PET – CT in the study of sarcomas began to appear after 2001 (Al-Ibraheem et al 2013; Aoki et al 2001, 2003; Benz et al 2009, 2010; Brenner et al 2004; Eary et al 1998, 2002; Feldman et al 2005; Folpe et al 2000; Garcia et al 1996; Purandare et al 2009; Schulte et al 1999). Some authors suggested that because PET – CT detects hyper metabolic foci, that whole body PET – CT could be an important test for identifying chondrosarcomas and their recurrence after surgery.…”
Section: Introductionmentioning
confidence: 99%